Accreditation as a Tool for Quality Assurance: The Roles of National Universities Commission (NUC) - Shuaib, Folorunsho Muhammed (International Journal of Educational Management, 2022)
Accreditation is a key to quality education in tertiary institutions in the country. This involves ensuring compliance with standards as prescribed by relevant regulatory agencies constituted by the Federal Government of Nigeria under the Federal Ministry of Education. The regulatory bodies that are constituted to accredit programmes/courses and ensure quality in the tertiary education are National Universities Commission (NUC) for universities education, National Commission for Colleges of Education (NCCE) for colleges of education programmes and National Board for Technical Education (NBTE) for polytechnics and other technical education. The paper therefore dealt with the roles of NUC, NCCE and NBTE on accreditation in ensuring quality, it also dealt with the accreditation parameters and status for the grading of accredited institutions. It was therefore concluded that accreditation exercise in the tertiary institution is a tool for quality assurance based on the roles play by these external regulatory agencies.